All‐fibre phase shifter based on tapered fibre coated with MoWS2‐rGO - Sin Jin Tan; Harith Ahmad; Zian Cheak Tiu (IET Optoelectronics, 2021)
Abstract In this work, an all‐fibre phase shifter using tapered fibre coated with molybdenum tungsten disulfide ‐ reduced graphene oxide (MoWS2‐rGO) is demonstrated. The large evanescent field of tapered fibre allows MoWS2‐rGO to absorb injected light from a 1400‐nm pump. It subsequently modifies the refractive index of both an MoWS2‐rGO solution and tapered fibre because of the thermo‐optic effect. A maximum wavelength shift of 2.489 nm is observed and the equivalent phase shift is 0.91π. The efficiency of the phase shifter is calculated at 0.0175 nm/mW. The proposed phase shifter is beneficial for a variety of applications, specifically for future optical beam‐forming networks and all optical signal processing devices.